2018
DOI: 10.1055/s-0038-1667121
|View full text |Cite
|
Sign up to set email alerts
|

Going Mobile: Resident Physicians' Assessment of the Impact of Tablet Computers on Clinical Tasks, Job Satisfaction, and Quality of Care

Abstract: The introduction of tablet computers enhanced resident physicians' perceptions of efficiency, effectiveness, and job satisfaction. Investments in this technology are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…As noted by Luff et al (1992), screen-based systems do tend to localize staff members to those screens, constraining locations of collaborations. This finding is further supported by previous studies reporting improved communication and workflow with mobile technology (Prgomet et al, 2009;Sweeney et al, 2018).…”
Section: Visual Connections Between Staff Worktations and Clinic Spaces And Observed Communication Frequencies Of The Spaces (Space Levelsupporting
confidence: 88%
“…As noted by Luff et al (1992), screen-based systems do tend to localize staff members to those screens, constraining locations of collaborations. This finding is further supported by previous studies reporting improved communication and workflow with mobile technology (Prgomet et al, 2009;Sweeney et al, 2018).…”
Section: Visual Connections Between Staff Worktations and Clinic Spaces And Observed Communication Frequencies Of The Spaces (Space Levelsupporting
confidence: 88%
“…The results showed that information quality and system quality were significant predictors of satisfaction, and, therefore, intention to use the system. 62 In addition, Li and Jiao 63 confirmed that there is a significant relationship between system quality and user satisfaction and that this relationship affects the actual use of online services. In addition, system quality perceptions have been reported to affect behavioral intention and usage decisions in many studies.…”
Section: M-health App Qualitymentioning
confidence: 98%
“…These tools and applications are frequently used during medical consultations (Sousa and Zaroukian 2003). Many of these mobile devices and applications have been shown to result in a variety of positive outcomes because of their capacity to assist in decision-making, facilitate care monitoring, and seamless access to reference material (Sweeney et al, 2018;Harper et al, 2019) For example, using of personal digital assistants (PDAs) positively influenced decision making and diagnostic tasks in several simulated patient cases (Coopmans and Biddle, 2008). Additionally, using electronic handheld devices for clinical reference resulted in improved patient safety, process improvement, increased quality care delivery, and safer care (Rothschild et al 2006;Patel et al 2012).…”
Section: Background Mobile Technology In Clinical Encountersmentioning
confidence: 99%
“…Thus, computing technologies can enhance the capacity of the physician during medical consultations (Sweeney et al, 2018). The potential benefit of improving the quality of care and operational efficiency make HITs appealing to many HMOs and primary care providers.…”
Section: Background Mobile Technology In Clinical Encountersmentioning
confidence: 99%
See 1 more Smart Citation